Comparison of Y-chromosomal haplogroup predictors. (December 2017) - Emmerova, Barbora; Ehler, Edvard; Comas, David; Votrubova, Jitka; Vanek, Daniel
Abstract: We used Y-chromosome DNA typing data from 342 unrelated individuals from the Czech Republic to obtain the Y-STR haplotypes and haplogroup-defining single nucleotide polymorphisms (SNPs). The resulting Y-STR haplotypes were subsequently entered into 5 different Y-haplogroup predictors (Vadim Urasin, Nevgen, Hapest, Jim Cullen, and Felix Immanuel), and the results were compared. We also evaluated the influence of the number of STRs used (12 vs. 19 loci) on the accuracy of the Y-haplogroup predictions.